DAMPAK PERILAKU KETERGANTUNGAN MEDIA SOSIAL FACEBOOK TEHADAP PRESTASI BELAJAR KOGNITIF PADA MATERI SISTEM PERIODIK UNSUR - Herniwati Herniwati; Kristianus Mite; Tamar Rumihin; Murtihapsari Murtihapsari; Christiana Niken Larasati (Universitas Papua, Manokwari, Indonesia, 2019)
Excessive use of Facebook social media among students is suspected to affect interest in learning and will have an impact on student learning achievement, especially on the material of the periodic system of elements. The purpose of this study includes the influence of Facebook social media addiction behavior on students' cognitive chemistry learning achievement. This study uses a quantitative method with an expost facto approach. The sampling technique used was purposive sampling using thirty respondents and data were collected using interviews, documentation and questionnaires. The results of this study indicate that there is an influence of Facebook's social media addiction behavior on cognitive chemistry learning achievement, which is 72%, while the relationship between Facebook's social media addiction behavior and cognitive chemistry learning achievement is related or correlated 0.852 which is categorized as very strong. Keywords: Behavior, facebook, achievement, learning